A comparable study on stray grain susceptibilities on different crystallographic planes in single crystal superalloys. (15th February 2021) - Guo, J.C.; Rong, P.; Wang, L.; Chen, W.J.; Han, S.X.; Yang, R.N.; Lei, X.W.; Yao, W.J.; Wang, N.
Abstract: The substrate orientation can affect the stray grain formation in laser remelted single crystal superalloys. A systematic investigation on the effect of substrate orientation on stray grain susceptibility was performed by varying laser scanning directions on three most conventional crystallographic planes (001), (011), and (111). We found that the scanning direction has a drastic effect on stray grain formation in (011) and (111) planes but shows less impact in (001) plane. The comparison of different planes reveals that the stray gain susceptibility in (011) plane is the weakest whereas that in (111) plane is the strongest. This can be attributed to the lower volume fraction of the local stray grains on the (011) plane. Our results show that stray grain can be depressed most effectively if a laser repair is performed in (011) plane along [100] direction, which can provide an in-depth insight into the mechanism of how to avoid stray grain formation in the future laser repair of single crystal components. Graphical abstracts: Image, graphical abstract